Relationship history of communication functions and decorated forms in architecture and design - Privoleva, S.; Tsiganok, A. (Theory and practice of design, 2016)
The article analyzes the relationship of function and decorated forms in architecture and design of different countries and times. Interaction function and decorated form predetermined internal logic of the development of architecture and arts and crafts. The history of the relationship functions and form also shows the impact on the architecture and design of certain socio-economic factors and the corresponding aesthetic views.